2021
DOI: 10.3390/ma14102516
|View full text |Cite
|
Sign up to set email alerts
|

Bending Fatigue Behaviour and Fatigue Endurance Limit Prediction of 20Cr2Ni4A Gear Steel after the Ultrasonic Surface Rolling Process

Abstract: To study the effect of the surface properties on the bending fatigue performance of heavy-duty gear steel, the authors of this paper used the ultrasonic surface rolling process (USRP) to strengthen 20Cr2Ni4A carburized gear steel. USRP is a novel technique in which the ultrasonic technology is incorporated into the concept of conventional deep rolling. In this study, we illustrated how the surface properties and cross-section mechanical property influence the three-point bending fatigue life of the samples bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This means that which range the rolling times is located in the surface of the material obtains better performance, which is a common multi-objective optimization problem in engineering applications, but he does not take into account. Wang et al [11] studied the effect of surface properties on the bending fatigue properties of heavy-duty gear steels. The results showed that the fatigue properties of the 20Cr2Ni4A material treated by ultrasonic rolling have a positive correlation with the surface roughness, surface residual stress and hardness.…”
Section: Introductionmentioning
confidence: 99%
“…This means that which range the rolling times is located in the surface of the material obtains better performance, which is a common multi-objective optimization problem in engineering applications, but he does not take into account. Wang et al [11] studied the effect of surface properties on the bending fatigue properties of heavy-duty gear steels. The results showed that the fatigue properties of the 20Cr2Ni4A material treated by ultrasonic rolling have a positive correlation with the surface roughness, surface residual stress and hardness.…”
Section: Introductionmentioning
confidence: 99%